2018
DOI: 10.1080/10242694.2018.1446241
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Consequences of the Libyan Spring: A Synthetic Control Analysis

Abstract: In 2011 a wave of revolutionary movements, the so-called Arab Spring, spread in the Middle East and North Africa. Libya was one of the most affected countries, ending Gaddafi's dictatorship after an international intervention and a civil war. This paper assesses the effects that this revolution had on Libyan economy. The analysis is made by means of the synthetic control method introduced by Abadie and Gardeazabal (2003). Our estimates for the 2011-2014 period show i) a cumulative loss in the growth rate of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In this respect, our findings are also similar to Lopez and Wodon (2005) who reported a permanent negative effect of the Rwanda genocide on per‐capita GDP in the range of 25%–30%. A related study showed that the effects of the Arab Spring on the Libyan economy resulted in a cumulative loss in the growth rate of GDP per capita of more than 64% during the 2011–2014 period, corresponding to a cumulative loss of real per‐capita GDP of more than US$56,000 and aggregate real GDP of more than US$350 billion (Echevarría & García‐Enríquez, 2019a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, our findings are also similar to Lopez and Wodon (2005) who reported a permanent negative effect of the Rwanda genocide on per‐capita GDP in the range of 25%–30%. A related study showed that the effects of the Arab Spring on the Libyan economy resulted in a cumulative loss in the growth rate of GDP per capita of more than 64% during the 2011–2014 period, corresponding to a cumulative loss of real per‐capita GDP of more than US$56,000 and aggregate real GDP of more than US$350 billion (Echevarría & García‐Enríquez, 2019a).…”
Section: Resultsmentioning
confidence: 99%
“…This approach is widely used in the literature and has more recently been followed by, among others, Hodler (2019), Matta et al. (2019), and Echevarría and García‐Enríquez (2019a).…”
Section: Data and Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…A representative, prominent example of such civil strife and unrest in the Middle East region is the Arab Spring. Depending on the country, it involved massive and often violent demonstrations and anti-government protests, uprisings and armed rebellions that affected many countries such as for instance Tunisia, Egypt, Bahrain, Oman, Yemen, Libya (inter alia: Cambrini and Zanotti, 2021;Matta et al, 2019;Hatab, 2019;Echevarr ıa and Garc ıa-Enr ıquez, 2019;Bettarelli, 2017;Anderson, 2011). However, as studies have shown the nexus between conflict and strife with the economy can be bidirectional.…”
Section: Introductionmentioning
confidence: 99%
“…A common cause identified in several studies was people's mistrust and disappointment in respective elite governments, unable to provide economic stability (Kireçci, 2020;Boucekkine et. al., 2016;Echevarría, & García-Enríquez, 2019). On the other hand, the COVID-19 pandemic has shaken the entire world and transformed every facet of society (Iacus et.…”
Section: Introductionmentioning
confidence: 99%